From conference to journal: Analyzing the path to publication for EUGA and JOGS 2022 abstracts - Rotem, Reut; O'Leary, Bobby D.; McCarthy, Claire M.; O'Reilly, Barry A.; O'Sullivan, Orfhlaith E. (International journal of gynecology and obstetrics, 2025)
Objective To determine the full‐text publication rate of s presented at the European Urogynaecological Association (EUGA) and the Junior Obstetrics and Gynecology Society (JOGS) annual scientific meetings in 2022, and to compare variables such as publication format, number of authors, and journal impact factor. Methods lists from the 2022 EUGA and JOGS meetings were reviewed. PubMed searches were conducted to identify corresponding full‐text publications up to August 2024 inclusive. Matches were determined based on substantial similarities in study title, authorship, and study design. Statistical comparisons were made using χ tests and Mann–Whitney U tests. Results A total of 304 s were included (138 EUGA, 166 JOGS), with an overall publication rate of 21.1%. EUGA had a significantly higher publication rate than JOGS (31.9% vs. 12.7%, P < 0.001). Oral presentations were more likely to be published than poster presentations (P < 0.001), with no significant difference in oral presentation publication rates between conferences (50% vs. 40%, P = 0.636). Poster presentations at EUGA had a higher publication rate than JOGS (22.3% vs. 8.9%, P = 0.006). s were more likely to be published if they had a greater number of authors (P < 0.001). The median journal Impact factor was 2.6, and 50% of published articles were open access. Conclusion International and national conferences play a crucial role in disseminating evidence, although just over one‐fifth of presented s progress to publication. A higher number of authors was associated with increased publication rates. Notably, oral presentations at both national and international levels were linked to favorable publication outcomes.